3D-printed microwell arrays for Ciona microinjection and timelapse imaging - Gregory, Clint; Veeman, Michael T. (My University, 2014)
Ascidians such as Ciona are close chordate relatives of the vertebrates with small, simple embryonic body plans and small, simple genomes. The tractable size of the embryo offers considerable advantages for in toto imaging and quantitative analysis of morphogenesis. For functional studies, Ciona eggs are considerably more challenging to microinject than the much larger eggs of other model organisms such as zebrafish and Xenopus. One of the key difficulties is in restraining the eggs so that the microinjection needle can be easily introduced and withdrawn. Here we develop and test a device to cast wells in agarose that are each sized to hold a single egg. This injection mold is fabricated by micro-resolution stereolithography with a grid of egg-sized posts that cast corresponding wells in agarose. This 3D printing technology allows the rapid and inexpensive testing of iteratively refined prototypes. In addition to their utility in microinjection, these grids of embryo-sized wells are also valuable for timelapse imaging of multiple embryos.
Keywords: Microinjection; 3D printing; Micro-resolution stereolithography